On the influence of zonal gravity wave distributions on the Southern Hemisphere winter circulation - Lilienthal, Friederike (2017)
A mechanistic global circulation model is used to simulate the Southern Hemisphere stratospheric, mesospheric, and lower thermospheric circulation during austral winter. The model includes a gravity wave (GW) parameterization that is initiated by prescribed 2-D fields of GW parameters in the troposphere. These are based on observations of GW potential energy calculated using GPS radio occultations and show enhanced GW activity east of the Andes and around the Antarctic. In order to detect the influence of an observation-based and thus realistic 2-D GW distribution on the middle atmosphere circulation, we perform model experiments with zonal mean and 2-D GW initialization, and additionally with and without forcing of stationary planetary waves (SPWs) at the lower boundary of the model. As a result, we find additional forcing of SPWs in the stratosphere, a weaker zonal wind jet in the mesosphere, cooling of the mesosphere and warming near the mesopause above the jet. SPW wavenumber 1 (SPW1) amplitudes are generally increased by about 10ĝ€% when GWs are introduced being longitudinally dependent. However, at the upper part of the zonal wind jet, SPW1 in zonal wind and GW acceleration are out of phase, which reduces the amplitudes there.